EFEKTIVITAS PIJAT BAYI (BABY MASSAGE) DALAM MENINGKATKAN KUALITAS TIDUR BAYI: STUDI KASUS DI PMB Bd. Fitri Yani, S. Keb PEKANBARU - Saukiah Salsa Billah Putri; Sarah Fitria (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Infant sleep quality is an important factor that supports the process of growth and development. Babies with poor sleep quality tend to be fussy, often wake up during the night, and feel uncomfortable while resting. One non-pharmacological approach that can be used to improve sleep quality and reduce fussiness in babies is infant massage. This study aims to determine the effectiveness of infant massage in enhancing sleep quality and reducing fussiness in Baby Ny. M at PMB Bd. Fitri Yani, S. Keb Pekanbaru. The research method used was a case study with a midwifery care approach. Data collection was carried out through interviews, observations, and monitoring of the baby's sleep patterns before and after the baby massage. The intervention was carried out routinely according to baby massage procedures. The results of the study showed an improvement in the quality of the baby's sleep after baby massage, characterized by longer sleep duration, deeper sleep, reduced frequency of waking at night, and the baby appeared calmer and less fussy. According to Mrs. M, the baby's mother, the baby's condition became more comfortable, cried less often, and was able to rest more easily after being given a massage. In addition to providing benefits for the baby, this condition also helps the mother in taking care of the baby so that she is not too overwhelmed. It can be concluded that giving a baby massage is effective in helping reduce fussiness in the baby and improving the baby's sleep quality to be more sound, comfortable, and of good quality.